2021
DOI: 10.1111/jcmm.16290
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles in chondrogenesis and Cartilage regeneration

Abstract: Cartilage is a hydrated tissue with no vascular and neural networks.They are divided into three major groups: hyaline, fibrous and elastic cartilages. Hyaline cartilage is the most frequent form and is found in synovial joints, ribs, nose, trachea, bronchi, etc 1 The main roles of this articular hyaline cartilage are to tolerate bone load and forming a lubricant environment to enable joint movement. 2 Extracellular matrix (ECM) synthesized by chondrocytes constitutes the main part of each cartilage. Collagen t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 111 publications
0
25
0
Order By: Relevance
“…Many studies have recently examined the potential use of exosomes as diagnostic markers and gene carriers for therapeutic purposes [ 66 ]. Exosomes (30–150 nm in diameter) are divided into three types: EVs’ micro-vessels/heading particles and apoptotic bodies (≥100 nm) [ 67 ].…”
Section: Application Of 3d Spheroid Culture System To Chondrogenic Di...mentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have recently examined the potential use of exosomes as diagnostic markers and gene carriers for therapeutic purposes [ 66 ]. Exosomes (30–150 nm in diameter) are divided into three types: EVs’ micro-vessels/heading particles and apoptotic bodies (≥100 nm) [ 67 ].…”
Section: Application Of 3d Spheroid Culture System To Chondrogenic Di...mentioning
confidence: 99%
“…MSC-exos have demonstrated excellent efficacy in tissue repair and reconstruction in a variety of organs [ 71 ]. Exosomes have been widely used by researchers for the treatment of autoimmune and inflammatory diseases such as osteoarthritis, because they play critical roles in the modulation of inflammation and immune responses (OA) ( Figure 4 ) [ 66 ]. However, large quantities of MSC-exos are required for preclinical and clinical research on exosome-based therapy.…”
Section: Application Of 3d Spheroid Culture System To Chondrogenic Di...mentioning
confidence: 99%
“…The above-mentioned MSCs and non-MSCs secreted EVs potentiate miRNAs-mediated epigenetic regulation in OA. Significantly, these studies have demonstrated the vital role of EVs-mediated miRNAs in cartilage destruction and regeneration, 20 synovial inflammation, 38 bone remodeling, 83 and the crosstalk among the above biological processes. 37 , 40 , 75 Therefore, this may provide an important target to observe the pathological process of OA and even a crucial breakthrough to the treatment of OA.…”
Section: The Application Of Evs-mirnas In Oa Treatmentmentioning
confidence: 99%
“…Nevertheless, it is beyond doubt that inflammatory processes in the synovial membrane play a crucial role in the initiation of OA and in promoting subsequent cartilage damage and pain at least in the inflammation-driven subset of patients ( de Lange-Brokaar et al, 2012 ). Therefore, the previously suggested differentiation potential of MSC into chondrocytes aiding cartilage regeneration ( Satué et al, 2019 ; Song et al, 2021 ) was pushed into the background against the ability of the MSC to target local immunocompetent cells.…”
Section: Targets and Mechanisms Of Msc In Tendon And Joint Diseasementioning
confidence: 99%